Cardiac Micro–Computed Tomography for Morphological and Functional Phenotyping of Muscle LIM Protein Null Mice - Cristian T. Badea; Laurence W. Hedlund; Julie F. Boslego Mackel; Lan Mao; Howard A. Rockman; G. Allan Johnson (Molecular Imaging)
The purpose of this study was to investigate the use of micro–computed tomography (micro-CT) for morphological and functional phenotyping of muscle LIM protein (MLP) null mice and to compare micro-CT with M-mode echocardiography. MLP null mice and controls were imaged using both micro-CT and M-mode echocardiography. For micro-CT, we used a custom-built scanner. Following a single intravenous injection of a blood pool contrast agent (Fenestra VC, ART Advanced Research Technologies, Saint-Laurent, QC) and using a cardiorespiratory gating, we acquired eight phases of the cardiac cycle (every 15 ms) and reconstructed three-dimensional data sets with 94-micron isotropic resolution. Wall thickness and volumetric measurements of the left ventricle were performed, and cardiac function was estimated. Micro-CT and M-mode echocardiography showed both morphological and functional aspects that separate MLP null mice from controls. End-diastolic and -systolic volumes were increased significantly three- and fivefold, respectively, in the MLP null mice versus controls. Ejection fraction was reduced by an average of 32% in MLP null mice. The data analysis shows that two imaging modalities provided different results partly owing to the difference in anesthesia regimens. Other sources of errors for micro-CT are also analyzed. Micro-CT can provide the four-dimensional data (three-dimensional isotropic volumes over time) required for morphological and functional phenotyping in mice.